Emergence of fosA3 and blaCTX–M–14 in Multidrug-Resistant Citrobacter freundii Isolates From Flowers and the Retail Environment in China - Cheng, Ke; Fang, Liang-Xing; Ge, Qian-Wen; Wang, Dong; He, Bing; Lu, Jia-Qi; Zhong, Zi-Xing; Wang, Xi-Ran; Yu, Yang; Lian, Xin-Lei; Liao, Xiao-Ping; Sun, Jian; et al. (Frontiers in Microbiology, 2021)
We examined the prevalence and transmission of the fosA3 gene among Citrobacter freundii isolates from flowers and their surrounding environments. We identified 11 fosfomycin-resistant C. freundii strains (> 256 µg/mL) from 270 samples that included petals (n=7), leaves (n=2), dust (n=1) and water (n=1). These 11 isolates were multidrug-resistant and most were simultaneously resistant to fosfomycin, cefotaxime, ciprofloxacin and amikacin. Consistently, all 11 isolates also possessed blaCTX-M-14, blaCMY-65/122, aac(6')-Ib-cr, qnrS1, qnrB13/6/38 and rmtB. These fosA3-postive isolates were assigned to two distinct PFGE patterns and one (n=9) predominated indicating clonal expansion of fosA3-positive isolates across flower markets and shops. Correspondingly, fosA3 was co-transferred with blaCTX-M-14 via two plasmid types by conjugation possessing sizes of 110 kb (n=9) and 260 kb (n=2). Two representatives were fully sequenced and p12-1 and pS39-1 possessed one and two unclassified replicons, respectively. These plasmids shared a distinctive and conserved backbone in common with fosA3-carrying C. freundii and other Enterobacteriaceae from human and food animals. However, the fosA3-blaCTX-M-14-containing multidrug resistance regions on these untypable plasmids were highly heterogeneous. To the best of our knowledge, this is the first report of fosA3 and blaCTX-M-14 that were present in bacterial contaminants from flower shops and markets. These findings underscore a public health threat posed by untypable and transferable p12-1-like and pS39-1-like plasmids bearing fosA3-blaCTX-M-14 that could circulate among Enterobacteriaceae species and in particular C. freundi in environmental isolates.